Teacher Work and Job Satisfaction among Romanian Lower Secondary Teachers - Zoller, Katalin; Bacskai, Katinka (Central European Journal of Educational Research, 2020)
The purpose of this paper is to provide an empirical based understanding of the Romanian context of teacher work, which provides an opportunity to identify characteristics considered to affect teaching activities and gives a basis for planning and conducting other research on teachers working conditions. The paper is based on authors' research which is a secondary analysis of Teaching and Learning International Survey (TALIS) 2013 database. The database contains the survey responses of teachers of lower secondary education (ISCED 2) and the principals of their schools. During the investigation cross/tables, cluster analysis, linear and logistical analyses were used. Based on our research results, we can see that the factors attributed both to the individuals and to the elements of pedagogical culture show a strong correlation with the characteristics of the teaching and the satisfaction with the teaching. Considering the factors attributed to the individuals, professional development and the total career time is the most influential factor of job satisfaction and teacher’s self-efficacy. Among the variables included in the school culture dimension, the effectiveness of teacher work, the disciplined atmosphere, the values of student/teacher relationships and the positive effects of teacher-teacher relationships indicated satisfaction and self-efficacy.